Australian Black summer smoke signal on Antarctic aerosol collected between New Zealand and the Ross sea - Scalabrin, Elisa; Barbaro, Elena; Pizzini, Sarah; Radaelli, Marta; Feltracco, Matteo; Piazza, Rossano; Gambaro, Andrea; Capodaglio, Gabriele (Chemosphere, 2024)
Open biomass burning (BB) events are a well-known primary aerosol source, resulting in the emission of significant amount of gaseous and particulate matter and affecting Earth’s radiation budget. The 2019-2020 summer, known as “Australian Black Summer”, showed exceptional duration and intensity of seasonal wildfires, triggered by high temperatures and severe droughts. Since increasing megafires are predicted due to expected climate changes, it is critical to study the impact of BB aerosol on a large scale and evaluate related transport processes. In this study, five aerosol samples (total suspended particles with a diameter >1 μm) were collected during the XXXV Italian Expedition in Antarctica on board of the R/V Laura Bassi from 6th of January to 16th of February 2020, along the sailing route from Lyttelton harbor (New Zealand) to Terra Nova Bay (Antarctica). Levoglucosan and its isomers have been analyzed as markers of BB, together with polycyclic aromatic hydrocarbons (PAHs), sucrose, and alcohol sugars. Ionic species and carboxylic acids have been analyzed to support the identification of aerosol sources and its aging. Results showed high levoglucosan concentrations (325-1266 pg m-3) during the campaign, suggesting the widespread presence of smoke in the region, because of huge wildfire releases. Backward trajectories indicated the presence of long-range atmospheric transport from South America, probably carrying wildfires plume, in agreement with literature. Regional sources have been suggested for PAHs, particularly for 3-4 rings’ compounds; monosaccharides, sucrose, arabitol, and mannitol were related to marine and biogenic contributions. In a warming climate scenario, more frequent and extensive wildfire episodes are expected in Australia, potentially altering albedo, aerosol radiative properties, and cloud interactions. Therefore, it is crucial to strengthens the investigations on the regional climatic effects of these events in Antarctica.